The transformations of the French labor market, 2000–2021 - Philippe Askenazy (IZA World of Labor, 2022)
France has the second largest population of countries in the EU. Since 2000, the French labor market has undergone substantial changes resulting from striking trends, some of which were catalyzed by the Great Recession and the Covid-19 crisis. The most interesting of these changes have been the massive improvement in the education of the labor force (especially of women), the resilience of employment during recessions, and the dramatic emergence of very-short-term employment contracts (less than a week) and low-income independent contractors, which together have fueled earnings inequality.
Keywords: J01; J08; O52; 330; education; unemployment; short-term jobs; independent contractors; inequality; France